2021
DOI: 10.1186/s13099-021-00441-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and detection of plasmid mediated colistin resistance mcr-1 gene among Escherichia coli and Klebsiella pneumoniae isolated from clinical samples

Abstract: Background The prevalence of antimicrobial resistance (AMR) among Gram-negative bacteria is alarmingly high. Reintroduction of colistin as last resort treatment in the infections caused by drug-resistant Gram-negative bacteria has led to the emergence and spread of colistin resistance. This study was designed to determine the prevalence of drug-resistance among beta-lactamase-producing strains of Escherichia coli and Klebsiella pneumoniae, isolated from the clinical specimens received at a tert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 85 publications
3
15
1
Order By: Relevance
“…In this study, E. coli was the most predominant Gramnegative bacterial isolate whereas S. aureus was the predominant Gram-positive bacterial isolate. This finding was in line with other studies reported from different hospitals/ laboratory settings in Nepal (37)(38)(39)(40). Observation of higher number of Gram-negative bacterial isolates in clinical specimens in different studies conducted in Nepal indicates Gram-negative bacteria are emerging as important health-care associated problems (41,42).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, E. coli was the most predominant Gramnegative bacterial isolate whereas S. aureus was the predominant Gram-positive bacterial isolate. This finding was in line with other studies reported from different hospitals/ laboratory settings in Nepal (37)(38)(39)(40). Observation of higher number of Gram-negative bacterial isolates in clinical specimens in different studies conducted in Nepal indicates Gram-negative bacteria are emerging as important health-care associated problems (41,42).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, all the phenotypic MRSA had mec A gene but none of MSSA had mec A gene. Bacterial growth pattern in the present study is in concert with most of the past studies reported from Nepal, the predominant bacterial isolates identified being E. coli [ 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…As a result of this resistance, there is a rising global difficulty with choosing an effective antibiotic treatment for hospital-acquired infections [ 8 , 14 , 18 ]. The pathogen is also involved in the transmission of antibiotic-resistant genes from bacteria in the environment to clinically significant pathogens [ 10 , 40 ].…”
Section: Discussionmentioning
confidence: 99%